New web-based algorithm to improve rigid gas permeable contact lens fitting in keratoconus. - Ortiz-Toquero, Sara; Rodriguez, Guadalupe; de Juan, Victoria; Martin, Raul (Contact Lens & Anterior Eye, 2017)
Purpose: To calculate and validate a new web-based algorithm for selecting the back optic zone radius (BOZR) of spherical gas permeable (GP) lens in keratoconus eyes.Methods: A retrospective calculation (n=35; multiple regression analysis) and a posterior prospective validation (new sample of 50 keratoconus eyes) of a new algorithm to select the BOZR of spherical KAKC design GP lenses (Conoptica) in keratoconus were conducted. BOZR calculated with the new algorithm, manufacturer guidelines and APEX software were compared with the BOZR that was finally prescribed. Number of diagnostic lenses, ordered lenses and visits to achieve optimal fitting were recorded and compared those obtained for a control group [50 healthy eyes fitted with spherical GP (BIAS design; Conoptica)].Results: The new algorithm highly correlated with the final BOZR fitted (r2=0.825, p<0.001). BOZR of the first diagnostic lens using the new algorithm demonstrated lower difference with the final BOZR prescribed (-0.01±0.12mm, p=0.65; 58% difference≤0.05mm) than with the manufacturer guidelines (+0.12±0.22mm, p<0.001; 26% difference≤0.05mm) and APEX software (-0.14±0.16mm, p=0.001; 34% difference≤0.05mm). Close numbers of diagnostic lens (1.6±0.8, 1.3±0.5; p=0.02), ordered lens (1.4±0.6, 1.1±0.3; P<0.001), and visits (3.4±0.7, 3.2±0.4; p=0.08) were required to fit keratoconus and healthy eyes, respectively.Conclusion: This new algorithm (free access at www.calculens.com) improves spherical KAKC GP fitting in keratoconus and can reduce the practitioner and patient chair time to achieve a final acceptable fit in keratoconus. This algorithm reduces differences between keratoconus GP fitting (KAKC design) and standard GP (BIAS design) lenses fitting in healthy eyes.